Septimius Severus and the Province of Syria and Palestine - Grassigli, Gian Luca (O T I V M, 2023)
The paper aims to analyze the approach of Septimius Severus to the territories of the Near East and in particular to the provinces of Syria and Palestine, specifically in the light of the stereotyped concepts of East and West typical of the culture of the time.